A estética da Commedia dell Arte: contribuições para o ensino das Artes Cênicas - Vieira, Marcílio de Souza (2005)
Theatrical phenomenon borned in the Italy the Comedy dell Art concerned to it climax in the XVI century and spreading itself by the word than can be sight like the theatre base modern. Lasting parallel the conventional theatre since the three hundred years, this gender influenced significativly the making theatrical in the Europe graces the popular character of its simulation turned for the improvise. In spite of treat a theatric manifestation no more existing in the present time, we understand that the Comedy dell Art was constituted in one artistic language whose esthetics centralized in the popular fanciful and in the improvise permitted a rich possibility of verbal and not-verbal communication that today can to be taken again in contemporary productions theatricals. Departing of an approach of esthetics, this work has with purpose concentrate the references esthetics that configure that one artistic manifestation such that one references can contribute for the Arts teaches in the present times. We appeal the text and image of Comedy dell Art, such this historical reference that in context, with fountain investigated that mean and if complementary in one esthetic reflection for the creation of meaning diverse and news interpretations for the purpose investigated if having with base some analysis categories such as: the actor s body, the actuations spaces and the esthetics categories such the ugly, the comic and the absurd. To investigate the Comedy dell Art esthetic in the ambit of the teach of Arts Scenics is a manner of be understand the artistic universe of three century behind that can be meant, revived, in the marking possibilities of an art teach able to incentive the critical, the appreciation, the discussion and the transgression of instituted true. Having investigated the exhibition Comedy dell Art esthetic we rebound four stich that we judge significative for we think the Arts Scenics teach, they are: the articulation between actor s body, the text and the space actuation in the play; statement what it is given between actor s body and the on-looker and the every gesture that did share of scene in a popular scenic space; a conception actor s body that transgress with the true duty socially that is capable the to admit its dimension Dionysian, creative and ambiguous in the to do theatrical; the text conception that get beyond the ambit the word writing by the dramatist and talked by actors, if spreading the other elements significance in the scene like gesture, the parody, the recent news, the gags and the word used in the day-to-day; the scenic space like a statement symbolic between actors and on-looker that make a quality of amusement pact supported by the scenic true of artist that actuate in not usual spaces bid at an auctioning degrees of participation in the building the scenic phenomenon; and the importance of esthetics categories such as the ugly, the comic and the absurd, those categories that foundation like a do scenic transgressor make a possible exchange mutual between actor and appreciator. The statement of esthetics categories in joint continuous between the body, the text and the scenic space evident themselves in doing theatrical and in the its appreciation. We believe that the reflection esthetic about the Comedy dell Art in the arts class, consider the stich detached, can favor possibilities of to share discovery, ideas, feelings and attitudes, and can permit the observation of different stich of view, establishing the statement of individual with the group in a participative and democratic form